Strategic Planning and Economic Valuation for Slope Optimization in PIT X PT ABC - Khairunissa, Dzakkiyyah Nur; Faturohman, Taufik (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This research evaluates two strategic options to extend the life of PT ABC's mature Pit X coal mine beyond its 2027 closure date. The study compares a river relocation plan (Scenario 1) against an integrated approach adding slope depressurization (Scenario 2). The objective is to determine which strategy offers superior economic value under market and regulatory uncertainty. A mixed-methods framework combines PESTEL and VRIO analyses to assess external conditions and internal capabilities, followed by a detailed discounted cash flow (DCF) model using a 13.31% discount rate. Financial results indicate Scenario 2 delivers stronger performance, with an NPV of IDR 2,321.20 billion, an IRR of 60.46%, and a 1.96-year payback period, outperforming Scenario 1 (NPV: IDR 2,283.41 billion, IRR: 40.68%, payback: 7.29 years). The added value stems from improved slope stability, which reduces overburden stripping by 16.4%, increases coal recovery, and lowers land requirements. Sensitivity and Monte Carlo simulations confirm Scenario 2’s resilience, identifying production costs and export coal prices as key risk factors. The study provides an integrated strategic financial framework for evaluating mining optimization projects and offers PT ABC a clear recommendation to adopt the slope depressurization strategy. This approach maximizes economic returns while enhancing operational safety and long-term competitiveness.